Oocyte maturation in bitches - Pereira, L. M. C.; Bicudo, S. D.; Lopes, M. D. (Brazilian Coll Animal Reproduction, 2012)
The canine species has been used as an experimental model for preservation of endangered species. Biotechnologies of reproduction, such as in vitro maturation (IVM), have been used to meet this objective. Several protocols for in vitro embryo production (IVEP) in swine and bovine species have been adapted for canids. However, the highest rate reported for in vitro maturation in canids is only 39%, which is still lower than those in other species. Therefore, current research on assisted reproduction in canids have focused on several IVM protocols, including the addition of proteins, hormones, meiosis inhibitors, growth factors and antioxidants to the maturation media and the determination of suitable timing for culture, so that variables involved in the process can be fine-tuned. This review has the main objective of describing major developments and limitations in the process of oocyte maturation in bitches.